A Mouse Model for Binge-Level Methamphetamine Use - Shabani, Shkelzen; Houlton, Sydney K.; Hellmuth, Laura; Mojica, Erika; Mootz, John R. K.; Zhu, Zhen; Reed, Cheryl; Phillips, Tamara J. (Frontiers in Neuroscience, 2016)
Binge/crash cycles of methamphetamine (MA) use are frequently reported by individuals suffering from MA use disorders. An MA binge is self-reported as multiple daily doses that commonly accumulate to 800 mg/day (~10 mg/kg/day for a 170 pound human). A genetic animal model with a similar vulnerability to binge-level MA intake is missing. We used selectively bred MA high drinking (MAHDR) and low drinking (MALDR) mouse lines to determine whether several procedural variations would result in binge-level MA intake. Data were also collected in two progenitor populations of the MA drinking lines, the DBA/2J (D2) strain and the F2 cross of the D2 and C57BL/6J strains. The impact of 3 factors was examined: (1) concentration of MA in the two-bottle choice procedure used for selective breeding; (2) ratio of bottles containing MA vs. water, and (3) length of the withdrawal (or abstinence) period between MA drinking sessions. When MA concentration was progressively increased every 4 days in 20 mg/l amounts from 20 to 140 mg/l, maximum intake in MALDR mice was 1.1 mg/kg, whereas MAHDR mice consumed as much as 14.6 mg/kg. When these concentrations were tested in a multiple bottle choice procedure, the highest ratio of MA to water bottles (3:1) was associated with escalated MA intake of up to 29.1 mg/kg in MAHDR mice and 12.0 mg/kg in F2 mice; MALDR mice did not show a ratio-dependent escalation in MA intake. Finally, MAHDR and D2 mice were offered 3 bottles of MA vs. water at increasing concentrations from 20 to 80 mg/l, and tested under an intermittent 6-h withdrawal period, which was lengthened to 30 hours (D2 mice) or to 30 or 78 hours (MAHDR). D2 and MAHDR mice initially consumed similar amounts of 14-16 mg/kg MA, but D2 mice reduced their MA intake 3-fold after introduction of 30-h abstinence periods, whereas MAHDR mice retained their high level of intake regardless of withdrawal period. MAHDR mice provide a genetic model of binge-level MA intake appropriate for the study of associated MA-induced neurobiological changes and pharmaceutical treatments.